THE EFFECT OF CONTEXTUAL REDEFINITION STRATEGY (CRS) ON STUDENTS’ VOCABULARY IN READING COMPREHENSION AT THE 10th GRADE OF SMK NEGERI 2 SELAYAR - Insyirah, Lilih; Firman; Ariana (FKIP Unismuh Makassar, 2023)
This study aims to find out whether Contextual Redefinition Strategy (CRS) was effective to enhance vocabulary at the 10th grade of SMK Negeri 2 Selayar. This research used quasi experimental design. The population of this research was the tenth-grade students of SMK Negeri 2 Selayar which consisted of 60 students. The sample of this research was 40 students taken by purposive sampling technique. The researcher used vocabulary test as the instrument of this research. Based on the research findings, the result showed that using Contextual Redefinition Strategy (CRS) was effective to enhance students’ vocabulary. It is proved by the means score of post–test between experimental group and control group. The means score in experimental group before and after treatment (47.15 became 89.50) and in control group before and after treatment (44.05 became 59.40) Moreover, the findings revealed that p-value of post-test score was 0.000 with the level significance 5% (0.05). It can be concluded that p-value (0.000) < sig ɑ = (0.05, 5%). Then, the effect size gained was 2.8. Thus, it proved that Contextual Redefinition Strategy (CRS) was effective at a strong level on students’ vocabulary in reading comprehension.